Web-based adaptive testing system for C programming - Wong, Frankie Fai Kit (2014)
With the ever increasing amount of workload that students have during their college, students requires more and more time to recap, revise and reinforce their knowledge of each subject. However, the current self-practice and self-assessment approaches seldom cater to a student’s learning capability or ability. To cope with this problem, Computerised Adaptive Testing (CAT) and Test Paper Generation (TPG) techniques have been used to eliminate some of these restrictions.